2018
DOI: 10.1177/1742395318792068
|View full text |Cite
|
Sign up to set email alerts
|

How do facilitators of group programmes for long-term conditions conceptualise self-management support?

Abstract: Objectives Increasing self-management skills in people with long-term conditions is widely advocated in policies and guidelines. Group programmes are a common format; yet, how self-management support objectives are enacted in their delivery is poorly understood. Our aim is to explore the perspectives of group programme facilitators. Methods We undertook thematic analysis of transcribed data from in-depth semi-structured interviews with health professional facilitators (n = 13) from six diverse self-management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Thoits suggests support from similar others directly affects physical and mental health and indirectly buffers harmful physical and mental effects (27). However, research has shown health professional facilitators do not always prioritise this form of support and professional authority, evidence-based education and narrow biomedical conceptualisations of self-management support prevail (24,25,35). Little group-specific training of health professional facilitators has been found in the literature (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thoits suggests support from similar others directly affects physical and mental health and indirectly buffers harmful physical and mental effects (27). However, research has shown health professional facilitators do not always prioritise this form of support and professional authority, evidence-based education and narrow biomedical conceptualisations of self-management support prevail (24,25,35). Little group-specific training of health professional facilitators has been found in the literature (23).…”
Section: Discussionmentioning
confidence: 99%
“…The group programmes in our study were perceived by participants as prioritising health professional and medical authority over exploration and nurturing of support for mutual benefit among the group participants. The 'invisibility' of the support that participants perceived and valued highly from peers may pose difficulties for health professional facilitators in the programme frameworks and medical contexts they operate within, which frequently use measurable biomedical outcomes to define success (5,24). Practitioners facilitating group self-management support programmes should be aware of the limitations inherent in professional expertise revealed in this study to people seeking support with self-managing LTCs.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, studies of group-based chronic disease self-management programmes showed that groups helped enhance selfefficacy for using self-management and coping strategies by providing opportunities for sharing experiences, social comparisons, and support (Abraham & Gardner, 2009;Barlow, Bancroft, & Turner, 2005;Rogers, Gately, Kennedy, & Sanders, 2009). Yet, the potential benefits of group support may not always be maximized by group facilitators in such interventions (Borek et al, 2019;Hughes et al, 2018). Yet, the potential benefits of group support may not always be maximized by group facilitators in such interventions (Borek et al, 2019;Hughes et al, 2018).…”
Section: Design Qualitativementioning
confidence: 99%
“…Research has also shown that developing a shared social identity is important in promoting health and engagement with group interventions (Tarrant, Hagger, & Farrow, 2012;Tarrant et al, 2017). Yet, the potential benefits of group support may not always be maximized by group facilitators in such interventions (Borek et al, 2019;Hughes et al, 2018). Previous studies have explored participants' experiences of health interventions in general.…”
mentioning
confidence: 99%